2019
DOI: 10.3766/jaaa.18046
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Responses in Children with Auditory Processing Disorder

Abstract: The ASHA recommends including electrophysiological measures in an auditory processing disorder (APD) assessment battery, but few audiologists do so, potentially because of limited published evidence for its utility.This study compared the auditory brainstem responses (ABRs) of children with APD with age-matched children and adults.This study retrospectively examined the records of 108 children suspected of APD (sAPD) who had click-evoked ABRs recorded as part of their clinical assessment. Twenty adults and 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The term listening difficulties is increasingly being used to describe children who are observed to have atypical difficulty in understanding speech or other auditory stimuli, often for unknown reasons ( Dawes & Bishop 2010 ; Moore 2012 ; Ankmnal-Veeranna et al 2019 ; Boothalingam et al 2019 ; Moore et al 2020a ). It has also been suggested that listening difficulty replace the label auditory processing disorder ( Moore 2018 ).…”
Section: A Taxonomymentioning
confidence: 99%
“…The term listening difficulties is increasingly being used to describe children who are observed to have atypical difficulty in understanding speech or other auditory stimuli, often for unknown reasons ( Dawes & Bishop 2010 ; Moore 2012 ; Ankmnal-Veeranna et al 2019 ; Boothalingam et al 2019 ; Moore et al 2020a ). It has also been suggested that listening difficulty replace the label auditory processing disorder ( Moore 2018 ).…”
Section: A Taxonomymentioning
confidence: 99%
“…The click ABR is an objective electrophysiological test widely used to assess hearing threshold and brainstem neural integrity ( 46 , 47 ). Ankmnal-Veeranna et al retrospectively compared 108 children with sAPD and 22 normal children for auditory brainstem response recording ( 32 ). Recording of click ABR in this study consisted of a slow stimulus (13.3 beats/s) and a fast stimulus (57.7 beats/s) presented to the left and right ears via headphones at an acoustic stimulus of 80 dBnHL, and the typical clinical indexes (latency and interpeak interval of waves I, III, and V) were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities in the latencies and amplitudes of the ABR imply the impaired integrity of the auditory pathways ( 95 , 96 ). ABR matures earlier ( 32 ) and is not affected by the state of consciousness of the child; as such, ABR is clinically more useful for monitoring the integrity of the auditory nerve in infants and young children. Although click ABR may be a useful electrophysiological tool in detecting auditory nerve integrity, its use for the identification of children with APD has not been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that a recent auditory brainstem response (ABR) examination of children with a diagnosis of suspected APD was completed by Ankmnal-Veeranna et al (2019), finding that, when compared with a control group, 37% of the children with a suspected APD diagnosis had abnormal ABR, although the majority had normal ABR recordings, comparable to controls. We acknowledge that this provides hopeful progress in the effort to find an organic index test for APD, but the professions clearly have not reached that goal yet.…”
Section: Discussionmentioning
confidence: 99%